Comparative Analysis Between Chinese Words “突然”、“忽然”and Indonesian Words “Tiba-tiba”, “Mendadak”: 汉语词语“突然”，“忽然”与印尼语词语“Tiba-tiba” ,“Mendadak”对比分析 - Sally Aprianti Tania; Stephen Aji Wardana (Mandarinable: Journal of Chinese Studies, 2023)
Parasynonym is one of the main challenges in second language acquisition process. Chinese and Indonesian language also had many words which has similar meaning.  In this paper, we focused on the comparative analysis between Indonesian words "Tiba-tiba" and "Mendadak", and chinese words "突然" and "忽然" in the semantic, pragmatic and translation pattern. The study results shows that "突然" and "忽然" have the meaning of "unexpected", while "tiba-tiba","mendadak" means "unthinkable"; all four words can also mean "rapidly happens", but "突然" can also to emphasize "controllability and purpose", "transition" and "to a certain degree" ; "忽然" can only mean "variability" and "methodology"; "Tiba-tiba" can mean "transition", "degree", "methodality"; "mendadak" can mean "degree" and "method" and "Unexpected event". The aforementioned four words basically have a lot in common in terms of pragmatics and structure, but their difference is that "忽然" cannot be used with adverbs of degree, while "突然", "tiba-tiba" and "mendadak" can. Thus its may concluded that when facing parasynonym in second language acquisition process also need special attention in order to achieve better language mastery.